2017
DOI: 10.2174/1874210601711010266
|View full text |Cite
|
Sign up to set email alerts
|

The Coronal Tooth Fractures: Preliminary Evaluation of a Three-Year Follow-Up of the Anterior Teeth Direct Fragment Reattachment Technique Without Additional Preparation

Abstract: Objective:The aim of this research is to describe and to analyse the long-term results and the clinical steps of direct fragment reattachment technique with no additional tooth preparation, used to treat crown fracture. This technique achieves the clinical success, combining satisfactory aesthetic and functional results with a minimally invasive approach.Methods:The 3 years follow-up included 9 patients (5 males, 4 females) with coronal fracture. In all the cases the fragment was available and intact. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 16 publications
2
49
0
Order By: Relevance
“…Determining the restoration shade to be identical to that of the affected tooth in every situation is too difficult due to difference in the optical properties (Joiner 2004 One study demonstrated hyper sensitivity of the treated teeth after 3 years follow up (Giudice et al 2017). If the repaired tooth was restored with a post, its brightness and translucency will be decreased (Vijayaprabha et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Determining the restoration shade to be identical to that of the affected tooth in every situation is too difficult due to difference in the optical properties (Joiner 2004 One study demonstrated hyper sensitivity of the treated teeth after 3 years follow up (Giudice et al 2017). If the repaired tooth was restored with a post, its brightness and translucency will be decreased (Vijayaprabha et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Tooth fracture may be confined to enamel or enamel and dentin without pulp exposure; in this case it is classified as simple fracture. On the other hand, complicated fracture means involvement of the pulp in the fracture site (Giudice et al 2017). The treatment of the fracture teeth depends -a great extent -on the type of fracture if it is simple or complicated.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude of the density perturbations can be characterised by the parameter 34) and is observed to be A s ∼ 10 −9 [45]. For f A 6M P this can only be obtained at a higher scale of inflation with Λ A ∼ 10 16 GeV.…”
Section: Crit Bmentioning
confidence: 99%
“…In this framework, for order one couplings of similar strength to start with, the lightest mass eigenstate of the mediators can have exponentially small couplings to the SM particles due to the localization in the flavor space. The gravity dual of the clockwork scenarios in extra dimensional models with dilaton background have been discussed [2,3,4,5,6] and has drawn new attention recently. In this article, we review the basic idea of the clockwork mechanism and discuss the gauged U(1) clockwork in specific and illustrate some interesting examples to resolve some of hierarchy problems in particle physics.…”
Section: Introductionmentioning
confidence: 99%